(untitled) (Journal of Legal Studies, 2015)
Currently, corruption has been so generalized and sophisticated that threatens to undermine the own society structure. Corruption is a problem identified in all the countries. What changes is how we deal with it. Nevertheless, why is there so much corruption? Within the group of factors, it is possible to highlight the high bureaucracy that reduces the efficiency of the public administration; the presence of a slow Judiciary Branch which is very low is terms of efficiency, when reprimanding illicit practices that incite everything ending up in pizza (this sentence was literally translated from Portuguese, it does not exist in English, but it means that impunity prevails in Brazil.); the existence of a corporatist sense among the Administration industries in the public sector in relation to the private sector and so facilitating corruption. The penalty for corruption should be constrained to mechanisms that allow the system of criminal justice to carry out actions of arrest, prosecution, penalty and repair to the country. Combating corruption complies with the republican ideal for the reduction of costs in Brazil. Moralizing the public-private relations offers juridical security to the market. The fact that some countries, especially Brazil, are seriously combating against corruption brings hope, with an eye on a more rigid legislation and less bureaucratic as well, with the end of the corporatist sense and the equivalence of salaries between the public and private sector. We shall provide effective criminal, administrative and civil penalties of inhibiting nature for future action; we shall provide cooperation between the law applicator and the private companies; we shall prevent the conflict of interests; we shall forbid the existence of "black fund" at the companies and we shall encouraged the relief or reduction of taxes to expenses considered as bribery or other conducts related.